2022
DOI: 10.3390/biology11111639
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationship, SPAD Reading, and Soluble Sugar Content as Indices for Evaluating the Graft Compatibility of Citrus Interstocks

Abstract: The interstock, a stock between the rootstock and scion, has a significant regulatory effect on the stock and scion, and its function is highly dependent on graft compatibility. To assess the graft compatibility of the interstock and scion, ‘Yuanxiaochun’ was top grafted onto ‘Ponkan’, ‘Shiranuhi’, ‘Harumi’, ‘Tarocco’, and ‘Kumquat’. The results showed significant differences in the survival ratio and preservation ratio among different combinations. Grafting compatibility in the early stages of grafting was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Recent studies have reported that, SPAD reading which is an indicator of chlorophyll content or photosynthetic activity can be used as a compatibility indicator between scion and rootstocks [ 13 , 33 ]. Studies have shown that the differences in the effects of different rootstocks on the scion behavior are mainly appeared in the leaves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported that, SPAD reading which is an indicator of chlorophyll content or photosynthetic activity can be used as a compatibility indicator between scion and rootstocks [ 13 , 33 ]. Studies have shown that the differences in the effects of different rootstocks on the scion behavior are mainly appeared in the leaves.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with Moing et al [ 32 ]who found that, soluble sugars accumulated in the scion were coincided with grafting incompatibility, since rootstocks in more incompatible combinations resulted in more soluble sugar accumulation in the scion. More recently, Wang et al [ 13 ] reported that the lowest survival rate was recorded in ‘Harumi’ as an interstock in apple grafting which accumulated higher sugars content and showed smaller leaf area and symptoms of incompatibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation